Perspektif Kaidah Al-Masyaqqah Tajlibut-Taysīr terhadap Keabsahan Akad Otomatis pada Transaksi Digital - Shindy Aulia Natasya; Fathin Albiyan Tanjung; Abdul Rahman (Lembaga Yasin AlSys, 2025)
The development of digital technology has transformed the way people conduct economic transactions, including through the emergence of automatic contracts that are concluded when users press an approval button in digital systems. Although this mechanism offers convenience and efficiency, it raises questions regarding its conformity with the principles of Islamic law. This study aimed to analyze the validity of automatic contracts using the legal maxim al-masyaqqah tajlibut-taysīr, with an emphasis on how the principle of facilitation in fiqh can be applied in the context of digital transactions. This research employed a literature study method by collecting, examining, and synthesizing classical and contemporary fiqh works that discuss contracts and legal maxims. The findings indicate that automatic contracts can be considered valid as long as the pillars and conditions of a contract are fulfilled, including the presence of mutual consent (tarādin) between the parties and clarity of the transaction object. These findings provide a conceptual contribution by integrating fiqh discourse with the phenomenon of modern transaction digitalization, thereby offering a relevant perspective for the development of Islamic economic law in the digital era.